Optimizing Polymeric Nanoparticle-Based mRNA Gene Delivery Materials- Aiming to Control Cellular Glycosylation - Gu, Yifan (My University, 2025)
The ability to modulate cellular glycosylation through gene expression holds significant promise for advancing immunotherapies and precision medicine. In this thesis, we developed and optimized poly(lactic-co-glycolic acid) (PLGA)-based nanoparticles for mRNA delivery, aiming to establish a biocompatible platform for targeted glycosylation control. Messenger RNA was first condensed using poly(amidoamine) (PAMAM) dendrimers and then encapsulated into PLGA nanoparticles (NPs) using a modified double emulsion technique. The resulting mRNA-loaded NPs exhibited sizes ranging from 160–220 nm with favorable positive surface charge, and mRNA/PAMAM cargo loading of 20% regardless of the mRNA type. Confocal imaging confirmed successful intracellular delivery and protein expression in macrophage cells, while in vitro experiments indicated improved protection of mRNA from degradation and enhanced transfection stability compared to mRNA/PAMAM complexes alone. Collectively, this work presents a robust and scalable polymeric platform for mRNA delivery and demonstrates its potential in immune targeted applications. These findings offer a promising basis for future efforts to regulate glycosylation pathways via mRNA delivery.
Keywords: Nanoparticles; mRNA; Gene delivery; PLGA; PAMAM; Emulsion; Protein Corona